Comparative studies of the oxidation of MoSi2 based materials: Low-temperature oxidation (300–900 °C). (August 2017) - Samadzadeh, M.; Oprea, C.; Karimi Sharif, H.; Troczynski, T.
Abstract: Molybdenum disilicide (MoSi2 ) rapidly oxidizes at 400–600 °C, which given enough time, can lead to its disintegration. Above 1000 °C, MoSi2 exhibits better oxidation resistance due to the formation of a continuous SiO2 layer (or alumina layer for the materials doped with aluminum). However, during high-temperature service, the protective layer on MoSi2 could be damaged, e.g. due to erosion, volatilization, and micro-cracks in thermal cycling, or due to exposure to reducing atmospheres. In this study, the oxidation characteristics of MoSi2 based materials were investigated in air, with the pre-oxidized protective layer removed to simulate such surface damages. Five different, commercially available, MoSi2 based heating elements, i.e. Kanthal Super (labelled by the manufacturer as KS-1700, KS-1800, KS-1900, KS-ER and KS-HT) were exposed to 300 to 900 °C isothermally, for 12 to 240 h, and their mass changes determined. Scanning Electron Microscopy, Energy-dispersive X-ray spectroscopy, and X-ray diffraction analyzed the microstructure, chemical composition and phase composition of the oxidized samples. It was found that the oxidation behavior of the different materials under investigation depended strongly on their chemical and phase composition, exposure time and temperature. KS-ER, KS-1800 and KS-1700 showed better resistance against the low temperature (300 to 900 °C) degradation for up to 240 h, while KS-HT and KS-1900 underwent significant degradation after 240 h of air exposure within the same temperature range. For rapid comparison of the materials damage sensitivity we propose a novel Cumulative Mass vs Temperature Index CMTI, including both mass gain and loss at temperatures ranging from 300 to 900 °C. The index allows quick ranking of the materials under consideration. Highlights: Formation of MoO3 was observed at temperatures as low as 300 °C after 240 h. For rapid comparison of the materials damage sensitivity, a novel Cumulative Mass vs Temperature Index CMTI was proposed. The peak oxidation temperature of (Mo, W)Si2 containing materials was shifted to 600 °C. Mo (Si, Al)2 and MoSi2 showed considerably better oxidation resistance than (Mo, W)Si2 based materials at 300–900 °C.